Even–odd layer-dependent magnetotransport of high-mobility Q-valley electrons in transition metal disulfides - Zefei Wu (Nature Portfolio, 2016)
Few-layer transition metal dichalcogenides exhibit strong spin-valley entanglement and unconventional quantum Hall states, however their study has been limited by electron mobility. Here, the authors explore how quantum transport varies between even- and odd-layered systems of high mobility.